2011
DOI: 10.1007/s00405-011-1567-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional CT with virtual bronchoscopy: a useful modality for bronchial foreign bodies in pediatric patients

Abstract: Bronchial foreign bodies (FB) in children are difficult to diagnose when there is no witness to the aspiration event. The experience with three-dimensional CT and virtual bronchoscopic reconstruction (3D-CTVB) was reviewed for the diagnosis of bronchial FB in pediatric patients in this study. A retrospective review of ten pediatric patients (M:F = 5:5) who underwent rigid bronchoscopy by one otolaryngologist for the impression of a bronchial FB, at a tertiary training hospital, from February 2006 to September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…Although VB has been advocated to be useful in the detection of tracheobronchial anomalies, data on its diagnostic accuracy thus far is limited to the detection of fixed airway stenosis in adults [10][11][12] and foreign body aspiration in children. [20][21][22][23][24][25][26][27] There has been limited data on its accuracy in the detection of dynamic airway abnormalities such as tracheobronchomalacia in both adults and pediatrics. What is currently known is summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Although VB has been advocated to be useful in the detection of tracheobronchial anomalies, data on its diagnostic accuracy thus far is limited to the detection of fixed airway stenosis in adults [10][11][12] and foreign body aspiration in children. [20][21][22][23][24][25][26][27] There has been limited data on its accuracy in the detection of dynamic airway abnormalities such as tracheobronchomalacia in both adults and pediatrics. What is currently known is summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…A CTVB is another non-invasive, safe and sensitive diagnostic modality for a bronchial FB 13 14. In current practice, when a chronic bronchial FB is suspected, performing both, HRCT of the chest and CTVB, prior to rigid bronchoscopy, is recommended practice 12–14.…”
Section: Discussionmentioning
confidence: 99%
“…
We read with great interest the well-written manuscript by Jung et al [1], which reported their experience with multislice computed tomography (MSCT) and virtual bronchoscopic (VB) reconstruction for the diagnosis of bronchial foreign bodies (BFBs) in pediatric patients. They discussed the importance of an early diagnosis, as any delay may cause serious complications.
…”
mentioning
confidence: 98%